WOMEN’S CAREERS IN SCIENCE AND THE FAMILY: CHOICE OR COMPATIBILITY? - Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 2008)
The need of higher participation of women in science is discussed. At the same time, statistical results show that there is little increase of women’s participation, especially high positions. Results of qualitative survey “Women’s careers in science and high technology” are analysed from the perspective of reconciliation of scientific career and family obligations in Lithuania. The content analysis of the stories of respondents shows that women scientists deny discrimination in research environment. But at the same time they notice unequal conditions for women and men making career in science due to family obligations. They recognize that women become ahead of men during the beraks for child care. They also notice that there are some structural barriers connected with evaluation of certain scientific periods, if these periods coincide with child care leaves. But researchers in science regard family duties as purely female. Therefore they do not see any discrimination. But at the same they are in favour of promotion of women after child-care leave, without including these leaves into periods of evaluation of scientific production, and offering special grants, scholarships, training, etc. Based on the results of research, the author indicates obstacles for women’s careers in science on three levels. On macro (state) level – patriarchal attitudes towards gender roles of the society, and lack of child-care facilities. On mezzo (system of science) level – structural barriers, connected with evaluation of researcher for certain period, if this period involves child-care leave. On micro (researcher’s) level – patriarchal attitudes towards gender roles of researchers themselves.